Translation: linguistic and ethnical barrier - D A Gusarov (Russian Language Studies, 2014)
The research establishes that the text as a syntactical construction functions as a universal medium for meaning and ethnical information. Then in the course of translation a “linguo-ethnical barrier” acts an instrument, which gathers different nonlinguistic facts as a translator’s complex of presupposition.